The relationship between organizational policies and practices and work limitations among hospital patient care workers. Issue 8 (29th May 2018) - Sparer, Emily H.; Boden, Leslie I.; Sorensen, Glorian; Dennerlein, Jack T.; Stoddard, Anne; Wagner, Gregory R.; Nagler, Eve M.; Hashimoto, Dean M.; Hopcia, Karen; Sabbath, Erika L.
Abstract : Objective: We examined relationships between organizational policies and practices (OPPs) (safety practices, ergonomic practices, and people‐oriented culture) and work limitations in a sample of hospital workers. Methods: We used the 6‐item Work Limitations Questionnaire (WLQ) to assess workers' perceptions of health‐related work limitations. Self‐reported OPPs and the WLQ were collected from workers in Boston, Massachusetts ( n  = 1277). We conducted random‐intercept multi‐level logistic regression models for each OPP using stepwise selection of covariates. Results: As the unit‐average ergonomic practice score increased by one, the odds of a worker reporting work limitations decreased by approximately 39% ( P ‐value = 0.018), adjusted for job title, age, and body mass index. A similar relationship existed for people‐oriented culture ( P ‐value = 0.038). The association between safety practices and work limitations was similar, but not statistically significant. Conclusions: This study demonstrated the importance of workplace OPPs. OPPs that promote positive and supportive environments and that foster improvements in ergonomics may help reduce work limitations.